The Effect of Financial Literacy on Student Financial Management - Andini Nurwulandari (SEAN Institute, 2022)
The purpose of this research is to determine how improving students' financial literacy influences their money management habits. A questionnaire was utilised as a data gathering tool in this study. Students at Indonesian universities who met other criteria for participation were used as respondents. Both simple linear regression analysis and multiple linear regression were used to make sense of the data. The study found that students' spending habits changed significantly after they were taught about money management. A higher level of financial knowledge is correlated with responsible spending and saving habits. Based on the results of this study, it is suggested to hold financial literacy programs in tertiary institutions to increase students' understanding of finance. In addition, universities can also provide students with easier access to information and financial resources. These programs are expected to help students manage their finances better and prevent financial problems from occurring in the future.